Purification of arsenic-contaminated drinking water by Fe-Al-CO3 layered double hydroxide derived from secondary aluminum dross: adsorption and stabilization studies - Mohammad Bozorgi; Mostafa Mahinroosta; Ali Allahverdi (Scientific Reports)
Abstract This study aims to utilize secondary aluminum dross waste to synthesize Fe-Al layered double hydroxide (Fe-Al LDH) for efficient adsorption of arsenic from drinking water. The synthesis process was based on a multi-step hydrometallurgical approach, in which the aluminum content in the waste was first converted to sodium aluminate. This was followed by the transformation into Fe-Al LDH through a series of processes, including gelation, sol formation, simultaneous precipitation, and aging. A suitable crystal structure of the LDH adsorbent was successfully synthesized at a Fe: Al molar ratio of 3, a pH of 7, and an aging time of 12 h. The characterization tests revealed that the synthesized Fe-Al-LDH had an interlayer space of 7.5 Å, a specific surface area of ​​145 m2/g, and a pore volume of 0.57 cm3/g. The resulting Fe-Al-LDH was then used to adsorb arsenic from aqueous solutions. The results showed that the amount of arsenic adsorbed by the LDH was 0.144 mg/g at room temperature, the adsorbent dose of 0.5 g/L, pH = 7 and the initial arsenic concentration of 80 µg/L. The Fe-Al LDH reduced the amount of arsenic in the water below the standard value after a period of 40 min. In addition, the results showed that the Fe-Al LDH can stabilize arsenic species in its structure and thus prevent their re-release into the environment.